Reading Film as a Text: Hermeneutics of Suspicion from Film the Joneses - Anam, Rifqi Khairul (Gerakan Indonesia Kita, 2025)
Film, as a form of mass communication, is fundamentally a textual representation that communicates a specific message. The act of watching a film is fundamentally equivalent to perusing a book, as both mediums are designed to communicate a message. Analyzing a film involves the engagement of our entire repertoire of memories, which serves as the foundation for interpreting its significance. The objective of this research is to illuminate the significance of covert marketing and the hazards it presents by examining the material object of the film The Joneses through the lens of Paul Ricoeur's hermeneutics of suspicion and employing a content analysis approach. Film